EVALUATION OF GREEN GDP MEASUREMENT IN INDONESIA USING GREY SYSTEM APPROACH - Andistya Oktaning Listra; Ferry Prasetyia (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2020)
The objective of the research was to apply Grey System Theory Type GM (1,1) on the forecast and evaluation of Indonesia’s Green GDP accounting which mainly deals with systems that have limited data and asymmetric information. The data used in this research is secondary data obtained from Sucofindo. The result of Grey System Theory Type GM (1,1) show that the Mean Percentage Error (MPE) and mean absolute percentage error (MAPE) value which showed bias conditions and lack of accuracy. This result show that the status of natural resources and environmental condition in Indonesia which considered from its result still present the weakness of Indonesia’s Green GDP accounting. From that consideration, the reconstruction of Indonesia’s Green GDP accounting are needed by increasing of green economy efforts and policies